Application of Room Service SOP by Waiters and Waitress in Improving Guest Satisfaction at Hotel SWISS-BELCOURT Lombok - Budiman, Budiman; Hariani, Yuni Sulpia (Akademi Komunitas MAPINDO, 2024)
The purpose of this study is to determine the process of room service by waiters and waitresses at Swiss-Belcourt Lombok Hotel and to find out the obstacles faced by a waiter and waitresses at Swiss-Belcourt Lombok Hotel. In this study using qualitative research, the location of this research was conducted on Jl. Raya Bypass BIL Km.2 Praya, Central Lombok West Nusa Tenggara. The types of data used in this study are qualitative and quantitative. The data sources in the study are as follows. Primary data sources and secondary data sources, while the research informants in this study were waiters and waitresses at the Swiss-Belcourt Lombok hotel. This study used purposive sampling in determining the number of research informants totaling 10 workers at the swiss-belcourt Lombok Hotel. Several stages will be carried out in this study, related to data collection are as follows, namely interviews, observation, documentation, and literature study, and for the data analysis method in this study using qualitative descriptive analysis. The results of this study show that room service at Swiss-Belcourt Lombok Hotel emphasizes that every step, from order taking to serving, is very important to achieve guest satisfaction. Efficient and friendly service, as well as attention to food quality and presentation, contribute to such satisfaction, while for the obstacles faced in providing room service, it is important to ensure that guests are satisfied.